MicroRNAs in Postischemic Vascular Repair - Andrea Caporali; Costanza Emanueli (Cardiology Research and Practice)
The term angiogenesis describes the growth of endothelial sprouts from preexisting postcapillary venules. More recently, this term has been used to generally indicate the growth and remodeling process of the primitive vascular network into a complex network during development. In adulthood, angiogenesis is activated as a reparative process during wound healing and following ischemia, and it plays a key role in tumor growth and metastasis as well as in inflammatory diseases and diabetic retinopathy. MicroRNAs (miRNAs) are endogenous, small, noncoding RNAs that negatively control gene expression of target mRNAs. In this paper, we aim at describing the role of miRNAs in postischemic angiogenesis. First, we will describe the regulation and the expression of miRNAs in endothelial cells. Then, we will analyze the role of miRNAs in postischemic vascular repair. Finally, we will discuss the role of circulating miRNAs as potential biomarkers in ischemic diseases.